Liquid Crystals as a Vehicle for Croton tiglium L. Oil for Deep Chemical Peel Formulations - Anna Claudia Morais de Oliveira Capote; Patricia Mazureki Campos; Cecília Cardozo Costa; Nicole Ribas Modesto da Silva; Priscileila Colerato Ferrari; Marcelo Paulo Bueno da Silva; Carla Cristine Kanunfre; Francieli Kanunfre de Carvalho; Carlos Gustavo Wambier; Evelyn Assis de Andrade; Wendy Karen Strangman; Flávio Luís Beltrame (Brazilian Archives of Biology and Technology, 2023)
Abstract Historically, phenol/croton oil deep chemical peeling has been very effective and has generated excellent results compared to other formulas used in dermatological clinics. However, it can cause serious side effects in patients sensitive to phenol. Therefore, this study aimed to develop a liquid crystalline structure containing croton oil (without phenol) as well as to evaluate the physical characteristics and cytotoxicity of this new system. Rational proportions of the croton oil, purified water, and polyethylene glycol hexadecyl ether were designed through a partial phase diagram to obtain 26 formulations. After macroscopic analysis and polarized light microscopy evaluation, formulations with lamellar liquid crystalline phase (4 samples) were identified and chosen to determine pH, size, polydispersion index (PDI), zeta potential, and rheological behavior. After 48 hours, three samples presented phase separation. Formulation 8 remained stable, but hydroxyethyl cellulose (HEC, 0.5%, w/w) was added to the aqueous phase, to prevent coalescence. Sample 8A exhibited a pH compatible with the skin, nanometric size, narrow PDI, negative zeta potential, and stability throughout the study period. The addition of HEC improved the organization of the system, making the formulation more stable. The oil, fractions of the oil, and the sample exhibited increasing cytotoxicity, respectively. This result could be attributed to the fractionation process of the vegetal matrix, and the surfactant present in the formulation increased the cell membrane permeability. The proposed approach successfully achieved a physically stable liquid crystal system containing croton oil.